Storybook Influence on Science Concept Comprehension Through Curiosity of Fifth Grade Elementary School Student (Universitas Negeri Semarang, 2018)
The use of storybooks is rarely used in science learning. Though the storybook is able to help students construct the concept comprehension and the curiosity. The purpose of this research is to know the Influence of the storybook on science concept through curiosity as an intervening variable. This is quantitative expose facto research with the formulation of associative problem. Data of Science Concept Comprehension, storybook, and curiosity are successively obtained through the description test instruments, multiple choice test instruments, and observation instruments, and also analyzed by regression analysis and correlation analysis. Storybook and curiosity influenced Science Concept Comprehension, proven correlation analysis of 0.92 and t-tested by 15.14. With the value of 2.02 ttable, then the results show that the influence of storybook and curiosity is very strong and significant. In the joint influence, the dominance of storybook influence is very high and significant, evidenced by a partial correlation of 0.89 with a value of t-test of 12.20. While the dominance of the influence of curiosity is very low and not significant, with the result of correlation analysis -0.03 and t-test value of -0.20. These results indicate that the storybook has a powerful effect on Science Concept Comprehension. In the storybook's shared influence, curiosity has no big effect on Science Concept Comprehension. This research should give belief to elementary school teachers to use storybook in learning because it proved very influential towards understanding the Science Concept.